Microwave photon detection by an Al Josephson junction - Revin, Leonid S.; Pankratov, Andrey L.; Gordeeva, Anna V.; Yablokov, Anton A.; Rakut, Igor V.; Zbrozhek, Victor O.; Kuzmin, Leonid S. (Beilstein Journal of Nanotechnology, 2020)
An aluminium Josephson junction (JJ), with a critical current suppressed by a factor of three compared with the maximal value calculated from the gap, is experimentally investigated for application as a threshold detector for microwave photons. We present the preliminary results of measurements of the lifetime of the superconducting state and the probability of switching by a 9 GHz external signal. We found an anomalously large lifetime, not described by the Kramers’ theory for the escape time over a barrier under the influence of fluctuations. We explain it by the phase diffusion regime, which is evident from the temperature dependence of the switching current histograms. Therefore, phase diffusion allows for a significant improvement of the noise immunity of a device, radically decreasing the dark count rate, but it will also decrease the single-photon sensitivity of the considered threshold detector. Quantization of the switching probability tilt as a function of the signal attenuation for various bias currents through the JJ is observed, which resembles the differentiation between N and N + 1 photon absorption.
Keywords: aluminium; Josephson junction; microwaves; phase diffusion; photon counter; switching current distribution

(untitled) - Barbieri, R.; Braggio, C.; Carugno, G.; Gallo, C. S.; Lombardi, A.; Ortolan, A.; Pengo, R.; Ruoso, G.; Speake, C. C. (Phys. Dark Universe, 2017)

(untitled) - Crescini, N.; Alesini, D.; Braggio, C.; Carugno, G.; D’Agostino, D.; Di Gioacchino, D.; Falferi, P.; Gambardella, U.; Gatti, C.; Iannone, G.; Ligi, C.; Lombardi, A.; et al. (Phys. Rev. Lett., 2020)

(untitled) - McAllister, B. T.; Flower, G.; Ivanov, E. N.; Goryachev, M.; Bourhill, J.; Tobar, M. E. (Phys. Dark Universe, 2017)

(untitled) - Kuzmin, L. S.; Sobolev, A. S.; Gatti, C.; Di Gioacchino, D.; Crescini, N.; Gordeeva, A.; Il’ichev, E. (IEEE Trans. Appl. Supercond., 2018)

(untitled) - Inomata, K.; Lin, Z.; Koshino, K.; Oliver, W. D.; Tsai, J.-S.; Yamamoto, T.; Nakamura, Y. (Nat. Commun., 2016)

(untitled) - Gol’tsman, G. N.; Okunev, O.; Chulkova, G.; Lipatov, A.; Semenov, A.; Smirnov, K.; Voronov, B.; Dzardanov, A.; Williams, C.; Sobolewski, R. (Appl. Phys. Lett., 2001)

(untitled) - Baeva, E. M.; Sidorova, M. V.; Korneev, A. A.; Smirnov, K. V.; Divochy, A. V.; Morozov, P. V.; Zolotov, P. I.; Vakhtomin, Y. B.; Semenov, A. V.; Klapwijk, T. M.; Khrapai, V. S.; Goltsman, G. N. (Phys. Rev. Appl., 2018)

(untitled) - Guarcello, C.; Valenti, D.; Spagnolo, B.; Pierro, V.; Filatrella, G. (Nanotechnology, 2017)

(untitled) - Zgirski, M.; Foltyn, M.; Savin, A.; Norowski, K.; Meschke, M.; Pekola, J. (Phys. Rev. Appl., 2018)

(untitled) - Guarcello, C.; Braggio, A.; Solinas, P.; Giazotto, F. (Phys. Rev. Appl., 2019)

(untitled) - Guarcello, C.; Valenti, D.; Spagnolo, B.; Pierro, V.; Filatrella, G. (Phys. Rev. Appl., 2019)

(untitled) - Guarcello, C.; Braggio, A.; Solinas, P.; Pepe, G. P.; Giazotto, F. (Phys. Rev. Appl., 2019)

(untitled) - Anghel, D. V.; Kulikov, K.; Galperin, Y. M.; Kuzmin, L. S. (Phys. Rev. B, 2020)

(untitled) - Wallraff, A.; Duty, T.; Lukashenko, A.; Ustinov, A. V. (Phys. Rev. Lett., 2003)

(untitled) - Oelsner, G.; Revin, L. S.; Il'ichev, E.; Pankratov, A. L.; Meyer, H.-G.; Grönberg, L.; Hassel, J.; Kuzmin, L. S. (Appl. Phys. Lett., 2013)

(untitled) - Oelsner, G.; Andersen, C. K.; Rehák, M.; Schmelz, M.; Anders, S.; Grajcar, M.; Hübner, U.; Mølmer, K.; Il’ichev, E. (Phys. Rev. Appl., 2017)

(untitled) - Chen, Y.-F.; Hover, D.; Sendelbach, S.; Maurer, L.; Merkel, S. T.; Pritchett, E. J.; Wilhelm, F. K.; McDermott, R. (Phys. Rev. Lett., 2011)

(untitled) - Poudel, A.; McDermott, R.; Vavilov, M. G. (Phys. Rev. B, 2012)

(untitled) - Yu, H. F.; Zhu, X. B.; Peng, Z. H.; Cao, W. H.; Cui, D. J.; Tian, Y.; Chen, G. H.; Zheng, D. N.; Jing, X. N.; Lu, L.; Zhao, S. P.; Han, S. (Phys. Rev. B, 2010)

(untitled) - Yu, H. F.; Zhu, X. B.; Peng, Z. H.; Tian, Y.; Cui, D. J.; Chen, G. H.; Zheng, D. N.; Jing, X. N.; Lu, L.; Zhao, S. P.; Han, S. (Phys. Rev. Lett., 2011)

(untitled) - Longobardi, L.; Massarotti, D.; Rotoli, G.; Stornaiuolo, D.; Papari, G.; Kawakami, A.; Pepe, G. P.; Barone, A.; Tafuri, F. (Phys. Rev. B, 2011)

(untitled) - Lisitskiy, M.; Massarotti, D.; Galletti, L.; Longobardi, L.; Rotoli, G.; Russo, M.; Tafuri, F.; Ruggiero, B. (J. Appl. Phys., 2014)

(untitled) - Koval, Y.; Fistul, M. V.; Ustinov, A. V. (Phys. Rev. Lett., 2004)

(untitled) - Martinis, J. M.; Kautz, R. L. (Phys. Rev. Lett., 1989)

(untitled) - Vion, D.; Götz, M.; Joyez, P.; Esteve, D.; Devoret, M. H. (Phys. Rev. Lett., 1996)

(untitled) - Grabert, H.; Ingold, G.-L.; Paul, B. (Europhys. Lett., 1998)

(untitled) - Franz, A.; Koval, Y.; Vasyukov, D.; Müller, P.; Schneidewind, H.; Ryndyk, D. A.; Keller, J.; Helm, C. (Phys. Rev. B, 2004)

(untitled) - Massarotti, D.; Longobardi, L.; Galletti, L.; Stornaiuolo, D.; Rotoli, G.; Tafuri, F. (Low Temp. Phys., 2013)

Dynamics of Josephson junctions and circuits - Likharev, K. K. (Gordon and Breach Science Publishers, 1986)

(untitled) - Blackburn, J. A.; Cirillo, M.; Grønbech-Jensen, N. (Phys. Rep., 2016)

(untitled) - Longobardi, L.; Massarotti, D.; Stornaiuolo, D.; Galletti, L.; Rotoli, G.; Lombardi, F.; Tafuri, F. (Phys. Rev. Lett., 2012)

(untitled) - Kramers, H. A. (Physica (Amsterdam), 1940)

(untitled) - Hänggi, P.; Talkner, P.; Borkovec, M. (Rev. Mod. Phys., 1990)

(untitled) - Caldeira, A. O.; Leggett, A. J. (Phys. Rev. Lett., 1981)

(untitled) - Malakhov, A. N.; Pankratov, A. L. (Phys. C (Amsterdam, Neth.), 1996)

(untitled) - Malakhov, A. N.; Pankratov, A. L. (Adv. Chem. Phys., 2002)